The optimal anatomic site for a single slice to estimate the total volume of visceral adipose tissue by using the quantitative computed tomography (QCT) in Chinese population. Issue 11 (November 2018) - Cheng, X; Zhang, Y; Wang, C; Deng, W; Wang, L; Duanmu, Y; Li, K; Yan, D; Xu, L; Wu, C; Shen, W; Tian, W
Abstract Background/objectives To investigate the relationship between the cross-sectional visceral adipose tissue (VAT) areas at different anatomic sites and the total VAT volume in a healthy Chinese population using quantitative computed tomography (QCT), and to identify the optimal anatomic site for a single slice to estimate the total VAT volume. Subjects/methods A total of 389 healthy Chinese subjects aged 19–63 years underwent lumbar spine QCT scans. The cross-sectional area of total adipose tissue and VAT were measured using the tissue composition module of the software (QCT Pro, Mindways) at each intervertebral disc level from T12 /L1 to L5 /S1, as well as at the umbilical level. The total VAT volume was defined as the fat areas multiplied by the height of vertebral body for all six slices. Statistical analysis was performed to determine the correlation between single-slice VAT areas and the total VAT volume. Moreover, the optimal anatomic site for a single slice to estimate the total VAT volume was identified by multiple regression analysis. Results The cross-sectional area of VAT and subcutaneous adipose tissue (SAT) measured at each anatomic site was all highly correlated with the total VAT volume and the total SAT volume (r  = 0.89–0.98). Additionally, the VAT area measured at the L2 /L3 level showed the strongest correlation with the total VAT volume (r  = 0.98, P  < 0.001). Covariates including age, gender, BMI, waist, and hypertension make a slight effect on the prediction of the total VAT volume. Conclusion It is feasible to perform measurements of VAT area on a single slice at L2 /L3 level for estimating the total VAT volume.